Towards Transformation: Strategies for Facing the Challenges of the PBL Learning Model in Elementary School Social Studies Courses - Widiani, Ni Komang; Esaputra, I Nyoman Tri (Journal of Education Reseach and Evaluation, 2025)
Educators face significant challenges in acting as facilitators, assisting, exploring deeper understanding, and supporting student initiatives in the learning process. This study aims to analyze the challenges of the PBL model in elementary school social studies learning courses. This type of research is qualitative research using qualitative descriptive research methods. The population in this study were students of the Elementary School Teacher Education Study Program (PGSD). Data analysis was carried out interactively in the study. Activities in qualitative data analysis were carried out interactively and continued until completion. The results of this study provide a reasonably comprehensive picture that both lecturers and students experience several difficulties in implementing the problem-based learning (PBL) model, especially in the context of social studies learning. From the lecturer's side, they are faced with challenges in several important aspects that are the key to the success of the PBL model. One of the main challenges is designing problems relevant to students' daily lives so that learning becomes more contextual and meaningful. On the other hand, students also experience difficulties implementing the PBL model. This indicates a need for improved learning strategies, infrastructure support, and the development of lecturer and student competencies so that the implementation of PBL can run more effectively and provide optimal results.